Speech therapy assesement of non-nutritive sucking and neurodevelopment relationship in preterm children - Ordóñez-Miyar, Belén D.; Periáñez, José A.; Blanco, Dorotea; Romero-Gómez, Bárbara; Valverde-López, Belén; Vellosillo, Perceval; Carricondo, Francisco (Revista de Investigación en Logopedia, 2025)
Sucking is a reflex necessary for survival, and premature infants often have problems developing it. Furthermore, it is a primary expression of brain function, leading to an increasing number of studies linking it to general movements (GM) and later neurodevelopment. Currently, the most widely used tool for assessing this is the NOMAS scale, but sucking patterns described on this scale as disorganized show an unreliable correlation with neurodevelopment. Therefore, a more in-depth analysis of the evolution of non-nutritive sucking (NNS) in relation to GM was proposed, in order to provide early predictive value. For this purpose, a prospective longitudinal descriptive study was carried out, with 66 premature participants <32 weeks of gestation and/or <1500g at birth, without neurological or orofacial malformation or genetic diagnosis. The progression of NNS and GM was studied from birth to hospital discharge, and neurodevelopmental assessment was collected at 4 years of age. The data showed that gestational age at birth is an important factor in assessing the risk of subsequent neurodevelopmental disorders. The different SNN subtests showed different degrees of correlation, with the sucking pattern and rhythm being the most related to the absence of disturbance. The most immature infants (23-24 weeks) showed better outcomes than subgroups born later. In contrast, those born between 25-26 weeks were at greater risk of future disorders. The week of birth appears to be a determining factor in neurodevelopment, showing different developments in NNS, so it could be a complementary assessment to the GM. The present study provides knowledge in the early analysis of NNS and neurodevelopment, although it is necessary to carry out future research with larger samples and with greater control of all the influential variables.